2014
DOI: 10.1371/journal.pntd.0002679
|View full text |Cite
|
Sign up to set email alerts
|

Immunoepidemiological Profiling of Onchocerciasis Patients Reveals Associations with Microfilaria Loads and Ivermectin Intake on Both Individual and Community Levels

Abstract: Mass drug administration (MDA) programmes against Onchocerca volvulus use ivermectin (IVM) which targets microfilariae (MF), the worm's offspring. Most infected individuals are hyporesponsive and present regulated immune responses despite high parasite burden. Recently, with MDA programmes, the existence of amicrofilaridermic (a-MF) individuals has become apparent but little is known about their immune responses. Within this immunoepidemiological study, we compared parasitology, pathology and immune profiles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 57 publications
3
59
0
Order By: Relevance
“…The combination of stimuli from the filarial nematode and its bacterial endosymbiont Wolbachia could promote a cytokine milieu favourable for the induction of an IL-17-mediated immune response [22], but little is currently known about the actual presence and role of such a response in filariasis [23][24][25]. We identified IL-17A expressing neutrophils in Wolbachia-positive Onchocerca volvulus nodules from infected Cameroonian patients [26] using immunohistochemistry (IHC) staining with a commercially available antibody (R&D Systems, goat polyclonal anti-IL-17A, Nodules from patients infected with O. volvulus were surgically removed, fixed in 80% ethanol and paraffin-embedded as part of the evaluation of a phase II trial of doxycycline [26].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of stimuli from the filarial nematode and its bacterial endosymbiont Wolbachia could promote a cytokine milieu favourable for the induction of an IL-17-mediated immune response [22], but little is currently known about the actual presence and role of such a response in filariasis [23][24][25]. We identified IL-17A expressing neutrophils in Wolbachia-positive Onchocerca volvulus nodules from infected Cameroonian patients [26] using immunohistochemistry (IHC) staining with a commercially available antibody (R&D Systems, goat polyclonal anti-IL-17A, Nodules from patients infected with O. volvulus were surgically removed, fixed in 80% ethanol and paraffin-embedded as part of the evaluation of a phase II trial of doxycycline [26].…”
Section: Introductionmentioning
confidence: 99%
“…The specific ligands, however, remain unclear although potential candidates include the Wolbachia surface protein, which induces TLR activity in vitro and can elicit TNF release in PBMC from healthy individuals in a dose‐dependent manner . Moreover, PBMC from O. volvulus ‐infected individuals produce pro‐inflammatory cytokines when cultured with Wolbachia surface protein, and recently, a recombinant peptidoglycan‐associated lipoprotein (wPAL) elicited higher TNF responses in microfilaridermic individuals compared with amicrofilaridermic cohorts: following regression analysis this was shown to be dependent on the presence of Mf . In vitro experiments have shown that macrophages respond to Brugia malayi antigen or Wolbachia in a TLR2/TLR6‐dependent manner and ES62, a phosphorylcholine‐containing glycoprotein derived from the non‐ Wolbachia containing filarial nematode Acanthocheilonema viteae also signals via TLR4, indicating that the filariae contain TLR‐specific components themselves .…”
Section: Discussionmentioning
confidence: 99%
“…26 Moreover, PBMC from O. volvulus-infected individuals produce pro-inflammatory cytokines when cultured with Wolbachia surface protein, 26 and recently, a recombinant peptidoglycan-associated lipoprotein (wPAL) elicited higher TNF responses in microfilaridermic individuals compared with amicrofilaridermic cohorts: following regression analysis this was shown to be dependent on the presence of Mf. 49 In vitro experiments have shown that macrophages respond to Brugia malayi antigen or Wolbachia in a TLR2/TLR6-dependent manner 25 and ES62, a phosphorylcholine-containing glycoprotein derived from the non-Wolbachia containing filarial nematode Acanthocheilonema viteae also signals via TLR4, indicating that the filariae contain TLR-specific components themselves. 50 In vivo a study that focused on determining the role of TLR4 and the development of protective immunity noted that C3H/HeJ mice failed to develop immune-mediated larval killing, and spleen cells from those mice produced significantly higher levels of IL-5 upon antigen re-stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ivermectin-treated onchocerciasis patients the expression of immunity will change; with parasite clearance, depressed cellular responsiveness of both types 1 and 2 will reactivate to O. volvulus and to bystander antigens, while parasite-specific antibody responses will lessen gradually [13][14][15][16][17][18]. Cell culture supernatants were collected after 48 h and chemokine and cytokine secretion was quantified by specific enzyme-linked immunosorbent assay (ELISA) (R&D Systems).…”
Section: The Impact Of Ivermectin Treatment On M Perstansmentioning
confidence: 99%